The Educational and Learning Reality for the Emigrant StudentsA Field Study for Al-Takya Secondary School for both, boys and girls in Baghdad Al-Salam Camp in Baghdad - فالح احمد, هالة (Al-Adab Journal, 2018)
The research entitled " The Educational and Learning Reality for the Emigrant Students" a field study for Al-Takya Secondary school in Baghdad for both, boys and girls, in Al-Salam Camp in Baghdad, comes after a cohabiting for one studies year in the camp school with emigrant students both, the secondary and elementary students. For I have been nominated by the department of educational directing in the Directory of Education in Baghdad, the second Karkh, for a work field with some counselors both men and women, and with the help of Mercy Corps organization, to return back the students who escape from the school both the emigrants and the host people themselves. So, I have cohabited with them and had an overview of their life's condition, for the social, the psychological and the economic sides of their life and the changes that face them. Hence, we come with all hope to bring them out of their miserable life. So, we returned them back to their school seats. The good thing that happened is that they are very clever, they are the best among their mates, and they truly succeeded excellently in their studies in spite of all the fear of death that they faced because of their bad conditions.The study talked with the social, economical, teaching, educational, health and security sides of the students life, and reached at these results:the students' escape from schools is a fatal result of the bad conditions that they encountered when they left their home because of the invasion that happened to their cities. With lack of ability to concentrate on their studies. Furthermore, equating between how they live, in the one hand, and what they need of material and spiritual capability for their life to go on, on the other hand.The narrowness of their dwelling, exemplified by the tent, makes their level of studies lower which leads them to leave their school seats.The educational and learning situation in the camp school can hardly satisfy the needs of studies because it is affected by the circumstances of living in a camp.The death of one of the student's parents or the one who is responsible on him may be the reason behind leaving the school. So, the case of being orphan for students and being widow for mothers is considered as one of many reasons behind the social and psychological problems which also affects on the continuation of studying in general.There is a relationship between the conditions that surround the society from the economic, social and political sides and the educational real state of the emigrant students.There is a need for the educational service of the counselors, this service makes the students accept and realize the problems which in turn makes them overcome these hinders. In fact, these problems is the result of the invasion of some governorates by ISIS in 2014. In addition, the sectarianism violence that predominates Iraqi society plays a role in the appearance of these problems.Recommendations:The research reaches at these recommendationsThe importance of returning back the escaped students to their seats in their schools.To develop this programme to make it involve all the schools in Baghdad in addition to other schools in the freed governorates like; Saladin, Al-Anbar and Ninva.To ask from the Directory of Education in Baghdad to offer financial fees to employ more counselors to remove the deficiency of counselors all over Iraqi schools.To let the counselors work in this field in their spring and summer holidays which doesn't accord to their jobs at schools.Due to the circumstances of wars, emigration and freeing then the returning back of emigrants to their home, there is a serious need for opening offices for educational directing and instructing in the residential areas supervised by municipal council with the help of the Directory of Education. In addition, broadening the directing and instructing departments to involve the students themselves with their families.To activate the role of the psychological and social supporting departments in the hospitals without restricting them to the psychologists, and then connecting these departments to the school health centers. After that, employ educational counselors in them.